Reinvestigation of Kuumbi Cave, Zanzibar, reveals Later Stone Age coastal habitation, early Holocene abandonment and Iron Age reoccupation. Issue 2 (2nd April 2016) - Shipton, Ceri; Crowther, Alison; Kourampas, Nikos; Prendergast, Mary E.; Horton, Mark; Douka, Katerina; Schwenninger, Jean-Luc; Faulkner, Patrick; Quintana Morales, Eréndira M.; Langley, Michelle C.; Tibesasa, Ruth; Picornell-Gelabert, Llorenc; et al.
ABSTRACT: The late Pleistocene and Holocene history of eastern Africa is complex and major gaps remain in our understanding of human occupation during this period. Questions concerning the identities, geographical distributions and chronologies of foraging, herding and agricultural populations — often problematically equated with the chronological labels 'Later Stone Age (LSA)', 'Neolithic' and 'Iron Age' — are still unresolved. Previous studies at the site of Kuumbi Cave in the Zanzibar Archipelago of Tanzania reported late Pleistocene Middle Stone Age (MSA) and LSA, mid-Holocene Neolithic and late Holocene Iron Age occupations (Sinclair et al. 2006 ; Chami2009 ). Kuumbi Cave considerably extends the chronology of human occupation on the eastern African coast and findings from the site have been the basis for the somewhat contentious identification of both a coastal Neolithic culture and early chicken, a domesticate that was introduced to Africa from Asia. The site therefore warrants further investigation. Here we report on a new excavation of the Kuumbi Cave sequence that has produced a suite of 20 radiocarbon and optically stimulated luminescence (OSL) dates. Our results suggest that the cave's stratigraphy is complex, reflecting taphonomic processes that present interpretive and dating challenges. Our assessment of the stratigraphic sequence demonstrates three phases of habitation, two of which reflect terminal Pleistocene occupation and are characterised by quartz microliths, bone points and the exploitation of terrestrial and marine species, and one of which reflects later reoccupation by AD 600. In this latter phase, Kuumbi Cave was inhabited by a population with a locally distinct material culture that included idiosyncratic Tana or Triangular Incised Ware ceramics and medium-sized limestone stone tools, but with a subsistence economy similar to that of the late Pleistocene, albeit with more emphasis on marine foods and smaller terrestrial mammals. Our results suggest that Kuumbi Cave may have been unoccupied for much of the Holocene, after Zanzibar became an island. Our findings also place into question earlier identifications of domesticates, Asian fauna and a mid-Holocene Neolithic culture at the site.